2019
DOI: 10.1155/2019/4546975
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the (Pro)renin Receptor on Cardiac Remodeling and Function in a Rat Alcoholic Cardiomyopathy Model via the PRR-ERK1/2-NOX4 Pathway

Abstract: Alcoholic cardiomyopathy (ACM) caused by alcohol consumption manifests mainly as by maladaptive myocardial function, which eventually leads to heart failure and causes serious public health problems. The (pro)renin receptor (PRR) is an important member of the local tissue renin-angiotensin system and plays a vital role in many cardiovascular diseases. However, the mechanism responsible for the effects of PRR on ACM remains unclear. The purpose of this study was to determine the role of PRR in myocardial fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The exact cause of ROS overproduction was not clear; however, several pathways crosstalk increased ROS production. The 5-FU-associated ET-1 elevation activates Nox 71,72 , and in a feedforward signal, ROS stimulate ET-1 via the MAPK/ERK1/2-dependent pathway to further mediate a negative impact on ECs 73 . Moreover, ROS activate other molecules, such as COX isoforms that also contribute to endothelial dysfunction 73 ; all of which are facts that support the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…The exact cause of ROS overproduction was not clear; however, several pathways crosstalk increased ROS production. The 5-FU-associated ET-1 elevation activates Nox 71,72 , and in a feedforward signal, ROS stimulate ET-1 via the MAPK/ERK1/2-dependent pathway to further mediate a negative impact on ECs 73 . Moreover, ROS activate other molecules, such as COX isoforms that also contribute to endothelial dysfunction 73 ; all of which are facts that support the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that extracellular signal-regulated kinases (Erk1/2) play a critical role in regulation of Nox4 expression [19]. We then explored the activation level of Erk1/2 at Thr202 and Tyr204 following 1 μM of Ang II treatment.…”
Section: Plos Onementioning
confidence: 99%
“…We constructed 3 short hairpin RNA (shRNA) fragments targeting PRR (Cao et al., ) which were encapsulated with recombinant adenovirus to form an adenovirus‐coated PRRshRNA fragment by Gene Pharma as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Sirius Red staining was performed to evaluate myocardial interstitial fibrosis. Immunohistochemical staining was performed as previously described (Cao et al., ). Serial sections were incubated overnight at 4°C with primary antibodies against rat collagen I (1:250, Abcam, ab34710), fibronectin (1:200, Abcam, ab32419), nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 (NOX2, 1:200, Proteintech, China, 19013‐1‐AP), 3‐nitrotyrosine (3‐NT, 1:200, Abcam, ab61392), 4‐hydroxynonenal (4‐HNE, 1:100, Bioss, Beijing, China, bs‐6313R), IL‐1 β (1:500, Abcam, ab8320), and IL‐6 (1:500, Abcam, ab6672).…”
Section: Methodsmentioning
confidence: 99%